Causal Effects of Inflammatory Arthritis Subtypes on Fibromyalgia: A Comprehensive Mendelian Randomization Study - Wang F; Jiang D; Zhang Z; Hu Z; Liang Y (Journal of Pain Research)
Fei Wang,1 Dengxu Jiang,2 Zhong Zhang,2 Zhengjun Hu,2 Yijian Liang1 1Department of Spinal Surgery, Chengdu BOE Hospital, Chengdu, People’s Republic of China; 2Department of Orthopaedics, The Third People’s Hospital of Chengdu/The Affiliated Hospital of Southwest Jiaotong University, Chengdu, People’s Republic of ChinaCorrespondence: Yijian Liang, Department of Spinal Surgery, Chengdu BOE Hospital, Chengdu, 610200, People’s Republic of China, Email yijiancq@163.comPurpose: Fibromyalgia (FM) is a chronic pain disorder characterized by widespread musculoskeletal pain and central sensitization, often co-occurring with inflammatory arthritis (IA) in clinical presentation. While observational studies suggest a higher prevalence of FM among IA patients, the causal relationship between IA and FM remains uncertain due to potential confounding factors and the possibility of reverse causation.Patients and Methods: We employed a two-sample Mendelian randomization (TSMR) approach to evaluate the causal effect of nine IA subtypes on FM, utilizing genetic summary data from large-scale genome-wide association studies (GWAS) encompassing up to 201,581 participants (exposure: IA phenotypes) and 168,378 participants (outcome: FM). The primary analysis was conducted using the Inverse-Variance Weighted (IVW) method, with sensitivity analyses assessing robustness and pleiotropy.Results: MR analysis revealed significant causal links between several IA subtypes and FM. Rheumatoid arthritis (OR 1.105, 95% CI 1.020– 1.198), enteropathic arthritis (OR 1.207, 95% CI 1.123– 1.299), Juvenile Idiopathic Arthritis (OR 1.307, 95% CI 1.183– 1.445), and other IA subtypes showed an increased risk of FM (all p< 0.0001). Psoriatic arthritis demonstrated no significant association with FM (OR 1.006, 95% CI 0.909– 1.112, p=0.911). Sensitivity analyses confirmed no significant heterogeneity and consistent results, despite minor horizontal pleiotropy observed in MR-Egger regression.Conclusion: This study provides genetic evidence supporting a causal relationship between IA subtypes and an increased risk of FM. However, no significant causal link was found between psoriatic arthritis and FM. These findings emphasize the role of immune-mediated inflammation in FM pathogenesis and highlight the differential impact of various IA subtypes on FM risk.Keywords: fibromyalgia, inflammatory arthritis, Mendelian randomization, genetic association, rheumatoid arthritis, psoriatic arthritis